Latihan Yoga Dapat Menurunkan Tingkat Kecemasan pada Siklus Mentruasi Remaja Puteri - Yulinda Yulinda; Dewi Purwaningsih; Cherly Marlina Sudarta (Alma Ata University Press, 2017)
Every month women aged 12-49 years, not pregnant and not yet experienced menopause has menstruation. During this period, problems experienced by many women are discomfort or pain. Dysmenorrhoea resulted absenteism and cause disadvantages, due to a temporary